Child-robot interaction in the wild: Advice to the aspiring experimenter - Ros,R; Nalin,M; Wood,R; Baxter,P; Looije,R; Demiris,Y; Belpaeme,T; Giusti,A; Pozzi,C (2011)
We present insights gleaned from a series of child-robot interaction experiments carried out in a hospital paediatric department. Our aim here is to share good practice in experimental design and lessons learned about the implementation of systems for social HRI with child users towards application in "the wild", rather than in tightly controlled and constrained laboratory environments: a trade-off between the structures imposed by experimental design and the desire for removal of such constraints that inhibit interaction depth, and hence engagement, requires a careful balance. © 2011 ACM.